Effects of transport and insertion of radio frequency identification (RFID) transponders on resistance and shape of natural and synthetic pebbles: applications for riverine and coastal bedload tracking. Issue 3 (1st August 2016) - Cassel, Mathieu; Piégay, Hervé; Lavé, Jérôme
Abstract: RFID transponders, especially low‐frequency Passive Integrated Transponders (PIT tags), are now commonly used for assessing bedload mobility in gravel‐bed rivers. Early studies reported high PIT tag recovery rates in small streams, but recovery rates in larger systems remain low. Explanatory factors for low recovery rates have been identified, but only antenna detection ranges and clustering effects have been precisely characterized. Burial below detection limit and dispersion beyond the study site have been indirectly estimated, and PIT tag destruction is assumed to be negligible. In this study, we quantified the resistance of natural limestone pebbles equipped with PIT tags as related to tag insertion methods and distance travelled in an annular flume. We then compared the performance of these natural pebbles with synthetic pebbles made of polyurethane resin and corundum. Creation of synthetic pebbles makes it possible to test bigger transponders with a greater detection range and no clustering effects, bypassing the existing constraints of RFID tracking. We found that breakage of limestone particles leading to PIT tag destruction is far too rare to explain low recovery rates in situ . Further, breakage is more affected by initial pebble characteristics than by PIT tag insertion method. Synthetic pebbles are more sensitive to attrition, but less likely to break. Natural and synthetic pebbles show slight differences in mobility patterns, transport distances, and abrasion resistances. One of the two synthetic pebbles travelled faster than the other three indicating that mobility is not only related to density but also potentially to shape. To address clustering and detection range issues, we equipped synthetic pebbles with AIT‐tags (Active Integrated Transponders). These were tested for integrity and transponder endurance and show great promise for future applications. Copyright © 2016 John Wiley & Sons, Ltd.